Hungarian Monitoring, 16 January 1988 . [Magyar rádiófigyelő], 1988. január 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Developments in the Argentinean coup attempt - USA space program to Moon and Mars - French presidential election - Cuba refuses participation in the Olympics Domestic Affairs: - Young Communist League (KISZ) central committee meeting - National Council of Trade Unions (SZOT) demands wages adjustments - The Béres case and the Celladam case - Returnees' property to be converted into Hungarian currency - Teaching Russian in schools: compulsory or optional? - Art and Revolution - Soviet exhibition in the Hall of Arts Economy: - Regulation restricting private imports Külpolitika: - Argentin puccskísérlet fejleményei - USA űrprogram a Holdra és a Marsra - Francia elnökválasztás - Kuba nem vesz részt az olimpián Belpolitika: - KISZ KB ülés - A SZOT bérigazításokat követel - Béres-ügy, Celladam-ügy - Forintosítják a hazatelepülők vagyonát - Orosz nyelvoktatás: kötelező vagy fakultatív? - Művészet és Forradalom: szovjet kiállítás a Műcsarnokban Gazdaság: - A magánimportot korlátozó rendelet